Efficacy and In Vitro Activity of Novel Antibiotics for Infections With Carbapenem-Resistant Gram-Negative Pathogens - Cruz-López, Flora; Martínez-Meléndez, Adrian; Morfin-Otero, Rayo; Rodriguez-Noriega, Eduardo; Maldonado-Garza, Héctor J.; Garza-González, Elvira (Frontiers in Cellular and Infection Microbiology, 2022)
Infections by Gram-negative multi-drug resistant (MDR) bacterial species are difficult to treat using available antibiotics. Overuse of carbapenems has contributed to widespread resistance to these antibiotics; as a result, carbapenem-resistant Enterobacterales (CRE), A. baumannii (CRAB), and P. aeruginosa (CRPA) have become common causes of healthcare-associated infections. Carbapenems, tigecycline, and colistin are the last resource antibiotics currently used; however, multiple reports of resistance to these antimicrobial agents have been documented worldwide. Recently, new antibiotics have been evaluated against Gram-negatives, including plazomicin (a new aminoglycoside) to treat CRE infection, eravacycline (a novel tetracycline) with in vitro activity against CRAB, and cefiderocol (a synthetic conjugate) for the treatment of nosocomial pneumonia by carbapenem-non-susceptible Gram-negative isolates. Furthermore, combinations of known β-lactams with recently developed β-lactam inhibitors, such as ceftazidime-avibactam, ceftolozane-tazobactam, ceftazidime-tazobactam, and meropenem-vaborbactam, has been suggested for the treatment of infections by extended-spectrum β-lactamases, carbapenemases, and AmpC producer bacteria. Nonetheless, they are not active against all carbapenemases, and there are reports of resistance to these combinations in clinical isolates.This review summarizes and discusses the in vitro and clinical evidence of the recently approved antibiotics, β-lactam inhibitors, and those in advanced phases of development for treating MDR infections caused by Gram-negative multi-drug resistant (MDR) bacterial species.